The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ajmg.b.32828
|View full text |Cite
|
Sign up to set email alerts
|

Mapping relationships between ADHD genetic liability, stressful life events, and ADHD symptoms in healthy adults

Abstract: Attention‐deficit/hyperactivity disorder (ADHD) symptoms are continuously distributed in the general population, where both genetic and environmental factors play roles. Stressful life events (SLEs) have been associated with ADHD diagnosis, but the relationship between ADHD genetic liability, SLEs, and ADHD symptoms in healthy individuals is less clear. Using a sample of 1,531 healthy adults (average age 26.9 years; 55.8% female), we investigated relationships between ADHD polygenic risk scores (ADHD‐PRSs), SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Environmental factors account for 10% to 40% of the variance associated with ADHD (Sciberras et al, 2017). Nevertheless, ADHD has an estimated high heritability of 76% (Khan & Faraone, 2006), and a complex relationship of environmental factors with genetic liability for ADHD has been reported (Li et al, 2021). Several prenatal risk factors have been shown to be associated with ADHD, such as maternal smoking, substance abuse, exposure to chemical toxins, maternal distress, and birth complications.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors account for 10% to 40% of the variance associated with ADHD (Sciberras et al, 2017). Nevertheless, ADHD has an estimated high heritability of 76% (Khan & Faraone, 2006), and a complex relationship of environmental factors with genetic liability for ADHD has been reported (Li et al, 2021). Several prenatal risk factors have been shown to be associated with ADHD, such as maternal smoking, substance abuse, exposure to chemical toxins, maternal distress, and birth complications.…”
Section: Discussionmentioning
confidence: 99%
“…PRS are less specific than previously thought, with large amounts of overlap across different NDDs and wider psychiatric and mental health conditions (e.g. Li, Franke, AriasVasquez, & Mota, 2021; Schork, 2018). These outcomes suggest that rather than detecting disorder‐specific mechanisms, PRS measures identify genes underpinning variations in cellular and biological pathways that confer a set of broader, transdiagnostic vulnerabilities.…”
Section: Transdiagnostic Mechanismsmentioning
confidence: 93%
“…ADHD presents one potential factor that may condition the effect of deviant peer association on dual systems cognitive development. As a disorder, ADHD is characterized by attention difficulties, impulsiveness, and hyperactivity, and may present a chronic course if left untreated in part because of genetic risk involved with the disorder (American Psychiatric Association, 2013; Li et al, 2021; Rasmussen and Levander, 2009). Although the prevalence of the disorder is approximately 5% in the general population of youths and higher than this among JIYs (Baglivio et al, 2017; Kaplan and Cornell, 2004), thus, presenting an issue facing a nontrivial amount of the young population, there remain numerous gaps in our understanding of the disorder with antisocial behavior.…”
Section: The Relevance Of Deviant Peers and Adhd For Predicting Dual ...mentioning
confidence: 99%
“…As noted previously, low impulse control is a hallmark feature of ADHD (American Psychiatric Association, 2013). Prior research has indicated a genetic characteristic of the disorder that may make these impulse control issues chronic (American Psychiatric Association, 2013; Li et al, 2021; Rasmussen and Levander, 2009). This is indicative of potential stability in levels of impulse control across the life course for individuals with the disorder.…”
Section: The Relevance Of Deviant Peers and Adhd For Predicting Dual ...mentioning
confidence: 99%